Life System Modeling and Intelligent Computing International Conference on Life System Modeling and Simulation, LSMS 2010, and International Conference on Intelligent Computing for Sustainable Energy and Environment, ICSEE 2010, Wuxi, China, September 17-20, 2010. Proceedings, Part III - Li, Kang.; Jia, Li.; Sun, Xin.; Fei, Minrui.; Irwin, George W. (Lecture Notes in Computer Science, 2010)
This book constitutes the refereed proceedings of the International Conference on Life System Modeling and Simulation, LSMS 2010, and the International Conference on Intelligent Computing for Sustainable Energy and Environment, ICSEE 2010, held in Wuxi, China, in September 2010. The 83 revised full papers were carefully reviewed and selected from numerous submissions.